Crossing thresholds : feminist essays in social history - Meera Kosambi (Orient Blackswan, 2007)
The notion of the threshold, indicating the restricted periphery of the woman s place in family and society, was firmly embedded in the psyche of nineteenth-century women in western India. Yet some remarkable and articulate women (who are the focus of this book) transgressed patriarchal boundaries crossing thresholds, literally and metaphorically to make their mark in the public sphere. These Indian women created the first ripple feminism of the region.